An IoT based Portable Air Quality Monitoring System with CO and CO2 Detector - Sitti Jubaira Umar; Ab Kadir, Diyana (Journal of Computing Technologies and Creative Content, 2020)
Air pollution gives large impact on life quality and poses a threat towards the ecosystem. Evolution in number of vehicles and industrial activities from day to day affect the air quality especially in urban areas. People cannot avoid of owning a vehicle but they can avoid carrying out an outdoor activity such as jogging, hiking or even picnic at the polluted air areas. This project is to develop a portable IoT based on air quality monitoring system with CO and CO2 detector by using Arduino microcontroller. User can monitor the air quality of the areas which they concerned by using this device. Most of the existing air pollution monitoring system is immobile and not concerning on monitoring the most harmful gases exist in atmosphere. This portable project focusing on a system that monitor air quality using MQ135, monitor temperature and humidity using DHT22 sensor as well as two of the most harmful pollutants exist, carbon monoxide and carbon dioxide using MQ7 and CO2 gas sensor. Next, the objective of developing this system is to analyze data collected from all sensors used within three days, at three different places, one day for each place. Data will be collected on 8am to 9am, 12pm to 1pm, 5pm to 6pm and 8pm to 9pm and the data collected will be displayed in the form of graph using ThingSpeak platform.